ALTERNATIVE CURRENCIES : MATHEMATICAL EXAMINATION - Gawthorpe, Kateřina; Pošta, Vít, 1980-; Macáková, Libuše, 1955-; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
This study provides a mathematical analysis for the current worldwide phenomenon of local currencies. The analysis outlines the impact evaluation of the coexistence of multiple currencies and provides a comparison of the outcome to a scenario where only one currency circulates. It also provides an answer for which form of currency, substitute or complement, is more beneficial for a community in terms of economic growth, economic and price stability, and resilience to exogenous shocks. The method of research consists of a regression analysis which serves as a background for a construction of a complex DSGE model. Evidence for the derivation of the simulation model relies on a case study with local currencies of the type used for Time banks in the United States and for example with the oldest currency, Switzerland’s Wirtschaftsring, in Switzerland. These case studies, along with a theoretical background of alternative currencies, necessitate a different structure of the model for complementary currencies and currencies which instead represent a substitute for a legal tender. The theoretical models for a complementary alternative currency, as well as for a currency of a substitute type are in the end applied to question potential benefits of the alternative-currency movement in the case of the Czech Republic.The conclusion of the thesis suggests a higher and more stable evolution of economic production in the presence of alternative currencies. Furthermore, economic output becomes more resilient towards exogenous shocks. The ultimate effect of alternative-currency demand also appears unambiguously beneficial for economic production. These findings stay valid also in the case of the Czech Republic. Next, the model for the Czech Republic shows lower inflation of the national currency in a multiple-currency scenario. The currency substitute reveals the character of an alternative currency for the Czech economy to be preferable.
The simulation model shows higher output and inflation stability along with more deepened resilience for the community when the currency substitute rather than complement circulates. The outcome of this thesis does not justify the skepticism of some monetary-policy and fiscal-policy makers towards the local-currency movement.
Vedoucí práce: Vít Pošta
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: ekonomie [obor disert. práce]; disertace; dissertations